Field measurements of particle dry deposition rates to foliage and inert surfaces in a forest canopy - Lindberg, Steven E; Lovett, Gary M (Environmental science & technology, 1985)
Development and application of a method for extraction and analysis of dry deposited material accumulated on individual growing leaves are describe d, and dry deposition rates of particulate sulfate, nitrate, potassium ion, and calcium ion to adjacent leaves and inert surfaces exposed simultane ously to ambient dry deposition are compared. The research was conducted at a mixed hickory-oak forest located in ridge-Valley terrain in rural Eastern Tennessee, within 22 km of two coal-fired utility powerplants. Continued development of foliar extraction methods and establishment of mathematical relationships between particle deposition rates to inert and foliar surfaces-if possible-and further investigations of deposition mechanisms in the canopy will aid in extrapolating point measurements of deposition to the full canopy. (1 diagram, 2 graphs, 1 photo, 36 referenc es, 1 table, )